PERANCANGAN SISTEM KEAMANAN RUANGAN MENGGUNAKAN RFID PADA E-KTP DI BALAI DESA SUKOREJO - Eko Siswanto; Nasrudin Nasrudin (STEKOM PRESS, 2018)
Increasing the level of crime and expertise of thieves is increasingly high, making writers get an idea or idea of ​​innovation of home door safety devices using Radio Frequency Identification (RFID) based on Arduino Uno which is certainly with a high security system. This security design does not rely on mechanics as its interface but instead uses electronic devices which are quite difficult to break into because besides required knowledge of electronics, criminals must also have knowledge in the field of programming and information technology. Unlike the mechanical lock, the electronic lock on this security design uses Radio Frequency Identification (RFID) as its opening. Based on the results of the test it can be concluded that the simulation of the safety device can operate properly, according to the design made. Rfid reader used has more secure security, because there is a keypad which to register the E-ID card, so not everyone can register an E-ID card, and there is also a buzzer, the buzzer will make a sound when the door is opened with a forced frequency of 13.56MHz placed in a miniature shaped house with a thickness of 2mm can read the E-ID ID with a maximum distance of 3.0 cm. Solenoid can open the door lock if the E-ID ID matches Arduino Uno, the solenoid will lock again within 5 seconds.